Think of a number and double it. (Economist, 2015)
The article focuses on the costs of cybercrime on businesses in 2015. Topics include the cost of security breaches, U.S. President Barack Obama's approval of the U.S. Personal Data Notification and Protection Act, and efforts to prevent computer hacking. Information is provided on state cybersecurity law in 2015.